Response of Shoot Growth of Pterocarpus indicus willd. to The Addition of BAP and TDZ In Vitro - Nofitria, Atika Sari; Violita, Violita; Novita, Linda; Hindaningrum, Irni Furnawanthi; Elya, Mardoni; Kartiman, Roni (Jurnal Biologi Tropis, 2024)
Pterocarpus indicus Willd. also known as redwood is a native Philippine species belonging to the Fabaceae family that has many uses and high economic value and highly exploited. However, it is not accompanied by good regeneration which causes this species to be categorized as endangered (IUCN v. 2021-1). The in vitro technique is an alternative to overcome this problem. This study aims to determine the response of P. indicus Willd. shoot growth to the addition of BAP and TDZ in vitro. The research was conducted from August to December 2023, at the Biotechnology Laboratory, KST BJ. Habibie Puspiptek Serpong, South Tangerang, Banten. This study used a completely randomized design (CRD) consisting of 9 treatments and 14 replications. The treatments consisted of: R0 = Control, R1 = BAP 0,25 ppm, R2 = BAP 0,5 ppm, R3 = BAP 0,75 ppm, R4 = BAP 1 ppm, R5 = TDZ 0,25 ppm, R6 = TDZ 0,5 ppm, R7 = TDZ 0,75 ppm, R8 = TDZ 1 ppm. The results showed that the concentration of BAP 0,5 ppm gave the best results in height of shoot and TDZ 0,25 ppm gave optimum results in the number of shoots compared to the control and other treatment concentrations.